2016
DOI: 10.1016/j.eurpsy.2016.01.1601
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism and Psychotic Symptoms: a Case Report

Abstract: IntroductionHyperthyroidism may lead to high anxiety status, emotional lability, irritability, overactivity, exaggerated sensitivity to noise, and fluctuating mood, insomnia and hyporexia. in extreme cases, they may appear delusions and hallucinations as psychiatric symptoms.Case reportwe report the case of a 53-year-old female who was diagnosed of hyperthyroidism and generalized anxiety disorder. The patient went to emergency department because of high levels of anxiety, with heart palpitations, trembling, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Previous studies have also shown that all three treatment methods (anti-thyroid medications, radioactive iodine, and surgery) show good results on the long-term quality of life of patients 28 . In some cases, anti-thyroid medication is most commonly given in patients with toxic adenoma, psychosis, fetal hyperthyroidism, fetal goiter, autoimmune, thyroid eye disease, and anxiety disorders 2,9,10,13,16,18 . Anti-thyroid medications that are widely used in the findings of the cases discussed are methimazole with varying doses of 0.5mg to 30mg/kg/day.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also shown that all three treatment methods (anti-thyroid medications, radioactive iodine, and surgery) show good results on the long-term quality of life of patients 28 . In some cases, anti-thyroid medication is most commonly given in patients with toxic adenoma, psychosis, fetal hyperthyroidism, fetal goiter, autoimmune, thyroid eye disease, and anxiety disorders 2,9,10,13,16,18 . Anti-thyroid medications that are widely used in the findings of the cases discussed are methimazole with varying doses of 0.5mg to 30mg/kg/day.…”
Section: Treatmentsmentioning
confidence: 99%
“…It is important to consider case findings in pregnant women with fetal hyperthyroidism or fetal goiter 3,11 . Hyperthyroidism occurs in 1-5% of neonates born to mothers with a history of Graves' disease 18 . Treatment with anti-thyroid medications such as methimazole or carbimazole is able to cross the placenta, which aims to maintain normal maternal and fetal thyroid function.…”
Section: Treatmentsmentioning
confidence: 99%